How can data contribute to Smart City innovation: a study from Thailand’s Smart City initiatives - Hansen, Michael Motet; Koonsanit, Kitti; Kulmala, Ville (Frontiers in Sustainable Cities, 2025)
Integrating data-driven technologies is increasingly crucial for developing Smart Cities, particularly in enhancing urban operations and ensuring inclusivity. As cities worldwide adopt Smart City initiatives, understanding the role of data in optimising urban infrastructure and services becomes paramount. This research addresses the challenge of effectively utilising data to support inclusive Smart City operations in Thailand. It focuses on real-time monitoring, resource optimisation, and community engagement to improve urban management and sustainability. The study employs a comprehensive review of Thailand’s Smart City initiatives, including using applications like Traffy Fondue. It analyses data from environmental sensors, community engagement tools, and governance platforms to assess their impact on city operations. The research also explores future directions by synthesising current practices and potential data infrastructure and analytics advancements. The findings reveal that data-driven strategies significantly enhance city operations by facilitating real-time issue resolution, informed decision-making, and efficient resource allocation. Integrating environmental monitoring systems and community engagement platforms further promotes sustainability and inclusivity. The study concludes that continued investment in data infrastructure, advanced analytics, and comprehensive data governance is essential. Future research should focus on developing scalable solutions, fostering global collaboration, and implementing supportive policies to maximise the benefits of Smart City technologies. This research provides a model for cities worldwide striving to improve urban environments through data-driven innovations.